A Rare Case of Unresectable Solitary Extramedullary Plasmacytoma at the Shoulder Region: Case Report - Putro, Yuni Artha Prabowo; Ekaputra, Ericko; Cein, C. Rayhan; Tampubolon, Yunus Oksikimbawan; Win, Raymond; Magetsari, Rahadyan; Dwianingsih, Ery Kus (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: Plasmacytoma is a solitary neoplastic lesion marked by a localized accumulation of monoclonal plasma cells without an evidence of a systemic proliferation. Plasmacytoma may arise in intramedullar (bone) or extramedullar (soft tissue). Extramedullary plasmacytoma is rare, with the most frequent locations in the nasal cavity and nasopharynx. Here, we describe a case of solitary extramedullary plasmacytoma of the shoulder region. CASE REPORT: A 49-year-old male patient presented with right shoulder mass that was solid, fixed, ulcerated, and poorly circumscribed, with size 20 × 15 × 10 cm. Shoulder X-ray and MRI results revealed a soft-tissue mass on the right shoulder with the destruction of lateral part of the right clavicle. Biopsy results suggested Non-Hodgkin Lymphoma; however, first panel of immunohistochemical (IHC) analysis showed negative staining of LCA, CK, CD20, and CD3, with high Ki67. Second panel of IHC revealed negative staining of ALK, TdT, and CD79a; meanwhile, CD138 was strongly expressed. Further hematological, biochemical, and radiological examinations that revealed no systemic involvement supported the diagnosis of solitary extramedullary plasmacytoma. Patient received radiotherapy treatment 60 Gy in 30 fractions and zometa within 4 weeks interval and showed remarkable response of the therapy. DISCUSSION: Solitary extramedullary (soft tissue) plasmacytomas (SEP) are less common than solitary bone plasmacytoma (SBP), yet it has a better prognosis since the majority can be cured by local radiotherapy. CONCLUSION: We report a case of SEP of the shoulder that showed remarkable response of therapy. In this case report, radiotherapy was shown to be a highly effective modality to treat a patient with solitary extramedullary plasmacytoma.